Modelling Web Services in the agent-oriented modelling language and environment CAMLE. (27th July 2007) - Zhu, Hong; Shan, Lijun
A particular difficulty in the development of Web Services applications is caused by the lack of communications between developers from different vendors. This paper investigates how modelling can help to solve the problem using the caste-centric agent-oriented modelling language and environment CAMLE, and illustrates the method by an example of online auction service. The use of CAMLE in model consistency check and specification generation is also discussed. Software engineers are enabled to specify not only the service provider's functionality and behaviour, but also the requirements and restrictions on service requesters' behaviours.